2022
DOI: 10.1111/odi.14374
|View full text |Cite
|
Sign up to set email alerts
|

Weakening of M1 macrophage and bone resorption in periodontitis cystathionine γ‐lyase‐deficient mice

Abstract: ObjectivesCystathionine‐γ‐lyase (CTH) has been proved to involve in inflammation and bone remolding, implying its potential role in the progression of periodontitis. This study was aimed to investigate the function of CTH and its relation to the macrophage polarization in periodontitis.Materials and methodsBone marrow‐derived macrophages (BMDMs) from wild‐type (WT) and Cth knockout (Cth−/−) mice were stimulated with lipopolysaccharide (LPS) in vitro and pro‐inflammatory cytokines were analyzed by qRT‐PCR. Liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…In vitro studies have indicated the critical role of macrophage polarization in the onset and progression of periodontitis [ 67 ]. The aforementioned results validate that inhibiting M1 macrophage polarization can reduce the expression of inflammatory cytokines in periodontal lesion tissues [ 74 ], and inducing M2 macrophages can prevent bone loss [ 75 , 76 ]. Therefore, CSBDX@MOF can promote alveolar bone regeneration by regulating M1/M2 polarization.…”
Section: Resultsmentioning
confidence: 59%
“…In vitro studies have indicated the critical role of macrophage polarization in the onset and progression of periodontitis [ 67 ]. The aforementioned results validate that inhibiting M1 macrophage polarization can reduce the expression of inflammatory cytokines in periodontal lesion tissues [ 74 ], and inducing M2 macrophages can prevent bone loss [ 75 , 76 ]. Therefore, CSBDX@MOF can promote alveolar bone regeneration by regulating M1/M2 polarization.…”
Section: Resultsmentioning
confidence: 59%
“…The onset of periodontitis is linked to the formation of M1 macrophages that are pro-inflammatory and can promote osteoclast differentiation by stimulating the production of RANKL. When M1 polarization is blocked, there is reduced periodontal bone loss ( 45 , 46 ). M2 macrophages exert anti-inflammatory effects in periodontal tissue by producing IL-10 and TGF-b ( 47 , 48 ).…”
Section: Innate Immunitymentioning
confidence: 99%